Salmon gill poxvirus, a recently characterized infectious agent of multifactorial gill disease in freshwater‐ and seawater‐reared Atlantic salmon. Issue 10 (20th January 2017) - Gjessing, M C; Thoen, E; Tengs, T; Skotheim, S A; Dale, O B
Abstract: Gill diseases cause considerable losses in Norwegian salmon farming. In 2015, we characterized salmon gill poxvirus (SGPV) and associated gill disease. Using newly developed diagnostic tools, we show here that SGPV infection is more widely distributed than previously assumed. We present seven cases of complex gill disease in Atlantic salmon farmed in seawater and freshwater from different parts of Norway. Apoptosis, the hallmark of acute SGPV infection, was not easily observed in these cases, and qPCR analysis was critical for identification of the presence of SGPV. Several other agents including Costia‐like parasites, gill amoebas, Saprolegnia spp. and bacteria were observed. The studied populations experienced significant mortalities, which increased to extreme levels when severe SGPV infections coincided with smoltification. SGPV infection appears to affect the smoltification process directly by affecting the gills and chloride cells in particular. SGPV may be considered a primary pathogen as it was often found prior to identification of complex gill disease. It is hypothesized that SGPV‐induced gill damage may impair innate immunity and allow invasion of secondary invaders. The distinct possibility that SGPV has been widely overlooked as a primary pathogen calls for extended use of SGPV qPCR in Atlantic salmon gill health management.